Refining direct cardiac reprogramming: modulation of mitochondrial metabolism and long non-coding RNAs - Santos, Francisco José Furtado (2024)
Cardiovascular diseases are among the leading causes of death worldwide. The associated pathology is characterized by loss of cardiomyocytes that eventually leads to heart failure. The mammalian neonatal heart possesses regenerative capacity, which is lost after birth when cardiomyocytes exit the cell cycle and shift their metabolism from glycolysis to OXPHOS. Besides bioenergetics, metabolites are important regulators of histone modifications, as they influence the activity of chromatin-modifying enzymes, thus linking metabolism, epigenetics and transcriptional regulation. Long non-coding RNAs (lncRNAs) have also emerged as critical regulators of gene expression. These RNA transcripts are devoid of coding potential, exhibit unique spatiotemporal patterns and have been implicated in heart development. Overexpressing cardiogenic transcription factors Mef2c, Gata4 and Tbx5 (collectively known as MGT) directly reprograms fibroblasts into induced cardiomyocytes (iCMs), providing means for replenishing the population of cardiomyocytes. This process, however, is stochastic and hampered by several barriers, including metabolic and epigenetic. Here, we show that the epigenetic transitions that occur during transdifferentiation of mouse fibroblasts into iCMs differ with age, possibly contributing to the lack of efficiency in adult cells. iCMs become increasingly engaged in mitochondrial respiration, but only those derived from embryonic cells remodel their mitochondrial network, with adult cells presenting higher levels of damaged mitochondria, possibly impacting the remodeling of the mitochondrial network. Promoting the clearance of damaged mitochondria, either by inducing mitophagy or dietary manipulations, improves reprogramming in adult cells, by a mechanism that might depend on ameliorating the quality and maturation of the mitochondrial network. This may result in the enhancement of OXPHOS and the availability of mitochondria-derived metabolites that can be used for metaboloepigenetic processes, thereby fine-tuning the transcription of not only cardiac-specific genes, but also those involved in mitochondrial dynamics and homeostasis. Furthermore, modulating the expression of lncRNA Phlda1-ot during direct cardiac reprogramming was shown to enhance generation of iCMs, possibly in a autophagy-inducing manner. highlighting the importance of autophagy during this process. In conclusion, the results presented in this thesis propose that modulation of metabolism and expression of lncRNAs both point to the regulation of autophagy, providing grounds for further investigation for improving direct cardiac reprogramming for regenerative purposes.